Ant return in rehabilitated mineral sand mines on North Stradbroke Island - Majer, Jonathan (1984)
The ant fauna of 12 sand mine plots representing a range of rehabilitation ages and three undisturbed vegetation controls was surveyed during 1982. Physical and botanical parameters were also measured in each plot. Sixty-four ant species were collected from the 15 study plots. Forty-four species had colonized one or more of the mine plots. Ant recolonization proceeded rapidly in plots up-to 6 years old and may have been influenced with time, by plant cover and diversity variables, the amount of litter and by the paucity of logs. The older plots exhibited a lower ant species richness and this is believed to have resulted from interspecific competition with the tramp ant species, Pheidole megacephala. Ant succession proceeded in a slower fashion in the P. megacephala dominated plots.